Transcranial Direct Current Stimulation on Different Targets to Modulate Cortical Activity and Dual-Task Walking in Individuals With Parkinson’s Disease: A Double Blinded Randomized Controlled Trial - Wong, Pei-Ling; Yang, Yea-Ru; Huang, Shih-Fong; Fuh, Jong-Ling; Chiang, Han-Lin; Wang, Ray-Yau (Frontiers in Aging Neuroscience, 2022)
Background. Transcranial direct current stimulation (tDCS) is a noninvasive brain stimulation to modulate cortical activity for improving motor function. However, the information of tDCS stimulation on different brain regions for dual task walking and cortical modulation in Parkinson’s disease (PD) has not yet been compared. Objective. To investigate the effects of different tDCS targets on dual task gait performance and cortical activity in patients with PD. Methods. 36 participants were randomly assigned to primary motor cortex (M1) tDCS, dorsal lateral prefrontal cortex (DLPFC) tDCS, cerebellum tDCS, or sham tDCS group. Each group received 20 min of tDCS stimulation, except the sham group. Gait performance was measured by GaitRite system during dual task walking and single walking. Corticomotor activity of tibialis anterior (TA) was measured using transcranial magnetic stimulation (TMS). The functional mobility was assessed using the timed up and go (TUG) test. Results. All participants showed no significant differences in baseline data. Following the one session tDCS intervention, M1 (P=0.048), DLPFC (P<0.001) and cerebellum (P=0.001) tDCS groups demonstrated significant improvements in dual task gait speed compared with pre-test. The time x group interaction (F(3,32)=5.125, P =0.005) were detected in dual task walking speed. The post-hoc Tukey’s test showed that the differences in gait speed was between sham tDCS group and DLPFC tDCS group (p=0.03). Moreover, DLPFC tDCS as well increased silent period more than M1 tDCS (p = 0.006) and sham tDCS (p = 0.002). Conclusion. Our results indicate that DLPFC tDCS exerted most beneficial effects on dual task walking and cortical modulation in participants with PD. Clinical Trial Registration: This trial was registered at the Thai Clinical Trials Registry (http://www.thaiclinicaltrials.org/show/TCTR20200909005).